Underpotential deposition and involved alloy formation of cadmium on silver particles modified HOPG substrates - Ambrusi, Rubén Eduardo (2018)
Cadmium underpotential deposition (UPD) on Ag particles modified highly ordered pyrolytic graphite (HOPG) surfaces, and the involved alloy formation were studied by conventional electrochemical techniques. Voltammetric results indicated that the Cd UPD followed an adsorption behavior different from that observed for massive Ag electrodes and Ag particles supported on vitreous carbon. Nanometer-sized bimetallic Cd–Ag particles were characterized by ex situ atomic force microscopy (AFM). Initially, AFM images show Ag deposits of similar size distributed preferably on HOPG step edges. No remarkable morphological changes are observed on the surface after the subsequent Cd deposition, suggesting that the Cd particles are deposited selectively over the Ag crystals. From the analysis of desorption spectra, employing different polarization times, and density functional theory (DFT) calculations, the formation of a Cd–Ag surface alloy could be inferred.